The single-cell landscape of cystic echinococcosis in different stages provided insights into endothelial and immune cell heterogeneity - Jiang, Xiaofeng; Zhang, Xiaofan; Jiang, Nan; Sun, Yeting; Li, Teng; Zhang, Jing; Shen, Yujuan; Cao, Jianping (Frontiers in Immunology, 2022)
Hydatid cysts and angiogenesis are the key characteristics of cystic echinococcosis, with immune cells and endothelial cells mediating essential roles in disease progression. Recent single-cell analysis studies demonstrated immune cell infiltration after Echinococcus granulosus infection, highlighting the diagnostic and therapeutic potential of targeting certain cell types in the lesion microenvironment. However, more detailed immune mechanisms during different periods of E. granulosus infection were not elucidated. We profiled the transcriptomes of 45,199 cells from the liver samples of nude mice at 1, 3, and 6 months after infection (two replicates) and uninfected wild-type mice. The cells were categorized into 26 clusters with four distinct cell types: natural killer (NK)/T cells, B cells, myeloid cells, and endothelial cells. An SPP1+ macrophage subset with immunosuppressive and pro-angiogenic functions was identified in the late infection stage. Single-cell regulatory network inference and clustering (SCENIC) analysis suggested that Cebpe, Runx3, and Rora were the key regulators of the SPP1+ macrophages. Cell communication analysis revealed that the SPP1+ macrophages interacted with endothelial cells and had pro-angiogenic functions. There was an obvious communicative relationship between SPP1+ macrophages and endothelial cells via Vegfa–Vegfr1/Vegfr2, and SPP1+ macrophages interacted with other immune cells via specific ligand–receptor pairs, which might have contributed to their immunosuppressive function. Our comprehensive exploration of the cystic echinococcosis ecosystem and the first discovery of SPP1+ macrophages with infection period specificity provide deeper insights into angiogenesis and the immune evasion mechanisms associated with later stages of infection.